2021
DOI: 10.2166/wst.2021.431
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of ZnO/CuO/Ag2O ternary metal oxide nanocomposite for effective photodegradation of organic water pollutants

Abstract: The current study is focused on fabrication of a ternary metal oxide nanocomposite (ZnO/CuO/Ag2O) as an efficient and superior photocatalyst by step wise implanting of p-type of CuO and Ag2O semiconductors onto n-type of semiconductor (ZnO) via chemical method. The structural and textural characteristics of manufactured samples were characterized by X-ray diffraction (XRD), Fourier Transform infrared (FT-IR) spectroscopy, field emission scanning electron microscopy combine electron dispersive spectroscopy (FES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 48 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…For ZnO and its nanocomposites on planar substrates, hours of UV radiation are needed for photodegradation. 31 Therefore, the photodegradation activity of AZO-decorated SuC-PCF is greatly improved since the surface−volume ratio is quite large and the liquid volume is small in SuC-PCF. After rinsing with deionized water and fulfilling with CV solution again, the SERS signal can be fully recovered, indicating that both AgNPs and ZnO nanorods preserve their functionality.…”
Section: Sers Performance and Photocatalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…For ZnO and its nanocomposites on planar substrates, hours of UV radiation are needed for photodegradation. 31 Therefore, the photodegradation activity of AZO-decorated SuC-PCF is greatly improved since the surface−volume ratio is quite large and the liquid volume is small in SuC-PCF. After rinsing with deionized water and fulfilling with CV solution again, the SERS signal can be fully recovered, indicating that both AgNPs and ZnO nanorods preserve their functionality.…”
Section: Sers Performance and Photocatalytic Activitymentioning
confidence: 99%
“…Therefore, ZnO is considered to be the main cause of CV photodegradation. For ZnO and its nanocomposites on planar substrates, hours of UV radiation are needed for photodegradation . Therefore, the photodegradation activity of AZO-decorated SuC-PCF is greatly improved since the surface–volume ratio is quite large and the liquid volume is small in SuC-PCF.…”
Section: Sers Performance and Photocatalytic Activitymentioning
confidence: 99%
“…The bulk band gap as Ag 2 O has a narrower band gap (2.84 eV) than ZnO (3.37 eV). The absorption intensity of ZnO is stronger than others in the visible region, suggesting an optimal electric surface charge of the oxide within the samples due to the introduction of the Ag 2 O which can possibly cause modifications of the fundamental process of electron-hole pair formation during irradiation [23,24].…”
Section: Resultsmentioning
confidence: 96%
“…Figure illustrates the UV–vis absorption spectrum and band gap of ZnO/CuO NCs. The presence of a peak around 462 nm indicates the formation of ZnO/CuO NCs, whereas individual UV–vis absorption spectra of ZnO and CuO solutions exhibit peaks around 271 and 368 nm, respectively . The UV–vis spectral results clearly indicated that a strong red shift has occurred in the ZnO/CuO nanocomposite case in comparison with the pure ZnO nanostructure.…”
Section: Results and Discussionmentioning
confidence: 99%